The Supersmart Dolphin - Schuh, Mari, 1975- (Minneapolis, MN : Lerner Publications, 2019)
Describes the physical features, life cycle, and sophisticated communication abilities of dolphins and the dangers they face from overfishing and pollution.
Meet the dolphin -- Smart dolphins -- The life of a dolphin -- Dolphins in danger -- Dolphin in diagram -- Fun facts -- Glossary -- Further reading -- Index.
Includes bibliographical references (page 23) and index.
Ages 6-9
K to grade 3.
Keywords: Dolphins; Dolphins -- Behavior -- Juvenile literature; Dolphins -- Psychology -- Juvenile literature; Dolphins -- Behavior; Juvenile works; Juvenile literature